The Performance and Design Checking of Chord-Angle Legs in Joist Girders - Galambos, Theodore V. (Engineering Journal, 2001)
The subject of this paper is the development of a design checking method for the capacity of the outstanding legs of the compression chord in joist girders subjected to eccentric reaction forces from the bearing seats of the joists bearing on these chords at panel points. Fifteen tests were performed, and, based on these tests and on plastic analysis, a conservative formula for the ultimate strength of the outstanding legs has been developed. A design checking formula is also proposed.